Medication and Dry Mouth: Findings from a Cohort Study of - W. Murray Thomson, BDS, MA, MComDent, PhD; Jane M. Chalmers, BDSc, MS; (Blackwell Synergy, 2000)
The aim of this study was to examine the association between medication exposure and (1) unstimulated whole-salivary flow rate and (2) the severity of xerostomia among olderpeople while adjusting for multiple medication use.